NILAI RELIGIUS DALAM FILM 3 DOA 3 CINTA - Nurfuadi Nurfuadi; Hendrix Agus Tian (IAIN Purwokerto, 2020)
The purpose of this study is to show the religious values found in teenage films of Islamic genre. This study uses a qualitative approach, using documentation data collection methods. The data source used in the study was an Indonesian film titled 3 Prayers 3 Love by director Nurman Hakim. The results of this study found that in film 3 prayer 3 love shows religious values, namely, the value of faith which includes faith in God, faith in angels, faith in the books, faith in the Rasul of Allah, faith in the end, faith in Qadha and Qadhar; and moral values which include morals to oneself in the form of courage and trust, not excessive to one thing, honest, sincere, and patient; morals towards parents in the form of devotion and loving parents; character of the family in the form of caring for and looking after family members; and morals to the community in the form of help and generosity.